Heterogeneous catalytic redox reactions : fundamentals and applications - Sadykov, Vladislav; Isupova, Lyubov A.; Tikhov, Serguei F. (De Gruyter, 2020)
The current book brings together cutting-edge research in the area of heterogeneous catalytic redox processes. The first part of the book covers the catalytic properties of transition metal oxides and the techniques for catalysts preparation, such as mechanochemistry, plasmochemistry, hydrothermal treatment, etc. Further the authors focus on mechanisms of heterogeneous redox reactions followed by the overview of industrial applications.